A polymorphism within the psoriasis susceptibility 1 candidate 1 (PSORS1C1) gene is not linked to HLA-B*58:01 in an Australian cohort. Issue 3 (June 2016) - Vidal, C.; Li, J.; Fulton, R.; Fernando, S.L.
Abstract: Association exists between HLA-B*58:01 allele and allopurinol Stevens-Johnson syndrome (SJS), especially those of an Asian heritage but associations have been also described in Caucasian populations. This creates the need to develop a rapid, robust and inexpensive assay for pre-screening of HLA-B*58:01. A polymorphism within PSORS1C1 gene was recently found in linkage disequilibrium (LD) with HLA-B*58:01 allele in the Japanese population. The aim of this study is to confirm whether this polymorphism can be used as a surrogate biomarker to identify carriers for HLA-B*58:01. No linkage was found between the two in the Australian cohort.